Migrant Parents and Their Views on Language and Parental Involvement: The Impact of an Embedded Language Course - Drijkoningen, Joke (LESLLA Symposium Proceedings, 2015)
The Parents in (inter)Action (PiiA) project was established in 2007 in a number of Flemish cities and communities, with the aim of breaking down barriers between migrant parents and their children’s school. It is an embedded Dutch as a Second Language (DSL) course for migrant parents, based in the primary school that their children attend. The project is run in partnership between the Centres for Adult Education and Basic Education that offer DSL courses and the primary schools. The PiiA concept was developed by the Centre for Language and Education at the University of Leuven. The positive evaluation that the project received following its first year, along with the positive experiences of the teachers (Colpaert and Strobbe 2009), demonstrated that its main goals had been achieved. However, to gain added insights, the Centre for Language and Education sought to gauge the parents’ views on the PiiA course and its impact in greater depth. This article highlights the results of the interviews we conducted with 66 parents (45 LESLLA learners).